PENGARUH PENGGUNAAN MEDIA KAHOOT TERHADAP SIKAP KERJASAMA SISWA DALAM PERMAINAN ICE BREAKING DI KELAS V SDN PONDOK RANJI 01 - Setiyaningsih, Dewi; Zahra, Lutfia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This research is motivated by the research hypothesis which suspects that there is an effect of using kahoot media on the cooperative attitude of fifth grade students in the ice breaking game. Aiming to get results is there any effect of using kahoot media on the attitude of student cooperation in the ice breaker game and how big is the effect. This research was conducted at SDN Pondok Ranji 01, South Tangerang. The method in this study is to use a survey method using a questionnaire in the instrument. The population in this study is 150 students of class V and to take samples, namely by taking two classes, namely as many as 60 students. the result of the calculation is that the value is Fcount > Ftable (38.127 > 3.92) then Ho is rejected and Ha is accepted. Thus the regression equation obtained has the influence of variable X (Kahoot Learning Media) on variable Y (cooperation attitude) and based on the coefficient of determination test that the Rsquare value is 0.243 or KD = 0.243 X 100% = 24.3%. This can be interpreted that the Kahoot Learning Media has an effect of 24.3% on the attitude of cooperation. While 75.7% is influenced by other variables that affect the attitude of cooperation.